Building a framework for theory-based ethnographies for studying intergenerational family food practices. (1st February 2016) - Visser, Sanne Siete; Hutter, Inge; Haisma, Hinke
Abstract: The growing rates of (childhood) obesity worldwide are a source concern for health professionals, policy-makers, and researchers. The increasing prevalence of associated diseases—such as diabetes, cardiovascular diseases, and psychological problems—shows the impact of obesity on people's health, already from a young age. In turn, these problems have obvious consequences for the health care system, including higher costs. However, the treatment of obesity has proven to be difficult, which makes prevention an important goal. In this study, we focus on food practices, one of the determinants of obesity. In recent years, it has become increasingly clear that interventions designed to encourage healthy eating of children and their families are not having the desired impact, especially among groups with a lower socioeconomic background (SEB). To understand why interventions fail to have an impact, we need to study the embedded social and cultural constructions of families. We argue that we need more than just decision-making theories to understand this cultural embeddedness, and to determine what cultural and social factors influence the decision-making process. By allowing families to explain their cultural background, their capabilities, and their opportunities, we will gain new insights into how families choose what they eat from a complex set of food choices. We have thus chosen to build a framework based on Sen's capability approach and the theory of cultural schemas. This framework, together with a holistic ethnographic research approach, can help us better understand what drives the food choices made in families. The framework is built to serve as a starting point for ethnographic research on food choice in families, and could contribute to the development of interventions that are embedded in the cultural realities of the targeted groups.